Sweden's Relative Economic Performance: Lagging Behind or Staying on Top? - Magnus Henrekson (The Research Institute of Industrial Economics (IUI), 1996)
The purpose of this papers is confined to illuminating the aspect: Has Sewedish economic growth been slow relative to other industrialised countries in recent decades, i.e. is Sweden lagging behind
Keywords: O10; O47; O50; 330; ECONOMIC GROWTH; ECONOMIC POLICY